2(12-8x)=x-11

Simple and best practice solution for 2(12-8x)=x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(12-8x)=x-11 equation:


Simplifying
2(12 + -8x) = x + -11
(12 * 2 + -8x * 2) = x + -11
(24 + -16x) = x + -11

Reorder the terms:
24 + -16x = -11 + x

Solving
24 + -16x = -11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
24 + -16x + -1x = -11 + x + -1x

Combine like terms: -16x + -1x = -17x
24 + -17x = -11 + x + -1x

Combine like terms: x + -1x = 0
24 + -17x = -11 + 0
24 + -17x = -11

Add '-24' to each side of the equation.
24 + -24 + -17x = -11 + -24

Combine like terms: 24 + -24 = 0
0 + -17x = -11 + -24
-17x = -11 + -24

Combine like terms: -11 + -24 = -35
-17x = -35

Divide each side by '-17'.
x = 2.058823529

Simplifying
x = 2.058823529

See similar equations:

| 3(5x+3)=4x+16-2x | | 4+2x=19-3x | | u+3=-4 | | x^5=59049 | | 0.57m=18-0.28m | | 275-3m+25m=x | | -12=2+5r+2r | | 4y-3=9+3(y-2) | | 6x+2x-2= | | 7x-2(3+2x)=3(4+x)-8 | | 6-5(k+1.1)=1.6 | | x+18=-5 | | (3x-2)(x^2-6x+2)= | | 11(z-5)=2(z+6) | | 10x-2(4x-9)=34 | | y-5=40 | | 4+6x=8x | | r=0.75r | | 4x+3x+300=12x | | X-4-x+4/3=0 | | -x+x= | | -0.625x=2y+11 | | 160m+215=1335 | | -2(4x-1)=-2 | | 5y-2=-9-2y | | 15x^2-25x^3=0 | | -(3a-5b+5c)= | | 65+x(x-5)=180 | | -7x-15+9x+23=2 | | r/2=11/8 | | 10b-2=4b-14 | | -(5x-10)=5 |

Equations solver categories